Innovative tele-ultrasound model for rural areas in Peru - Rojas-Mezarina, Leonardo (2018)
One of the main challenges of our health system is to meet the current and future needs of the sector by guaranteeing equitable access and quality to health services, so that in response to this need, the use of the capabilities provided by technologies arises. Therefore, this article describes an innovative model of tele-ultrasound implemented in various rural areas of Peru which consists of a new method of acquisition of images through volumetric protocols associated with correct operator training, the utilization of user-friendly equipment , as well as the cloud that allows diagnosis anywhere in the world. Likewise, the results of the interventions carried out with this new model are presented in different regions with rural areas of the country highlighting its advantages and limitations. This type of experience serves as an example of the usefulness of technology which can be replicated in other aspects of the health sector. Therefore, it is necessary to continue generating scientific evidence that provides the basis for the implementation of new public policies aimed at the promotion of this type of innovation.